Oversampling analog to digital conversion in acoustic measurements - KLECZKOWSKI, P. (Archives of Acoustics, 1993)
The new method of analog to digital conversion known as "oversampling" or "delta-sigma", is inherently more suitable for acoustics measurements than the traditional method was. The theoretical background of this new method is presented. Both methods of conversion are compared with reference to their use in acoustics. The tests of parameters important in processing of acoustics signals performed on monolithic "delta-sigma" converters are reported. A digital procedure for evaluating the THD+N parameter is proposed.